The Graphic Evaluation of Morphological Characters in Honey Bees (Apis mellifera L.) by Chernoff Faces - H. Vasfi Gençer (Journal of Agricultural Sciences)
Seven parent colonies and 5 offspring colonies of two different Anatolian honey bee (Apis mellifera anatoiiaca) ecotypes (total 24 colonies) were sampled randomly for morphological analysis. Morphometric measurements were made on 10 characters. A multivariate graphic methotf (Chernoff faces) was applied to data of parents and offsprings in representing morphometric data. This multivariate graphic technique, "Chernoff faces", couid dıstinguish differences between ecotypes and betvveen parents and offsprings enabling simpie and quick visual comparisons.